Insurgency, Activism, and Community Leadership in the Inclusion of Migrants in Portugal (Cadernos de Sociomuseologia, 2026)
This interview with Nilzete Pacheco, activist, community leader, and president of the Instituto Brasil, examines trajectories of activism, community leadership, and migrant inclusion in Portugal, with particular emphasis on immigrant women and entrepreneurship. The interview highlights the importance of representation, community insurgency, and inclusive pedagogy as strategic tools for promoting rights, citizenship, and autonomy. The testimony underscores the central role of migrant women in resisting structural inequalities and in producing hybrid forms of knowledge, as well as the persistent need for greater representation in museums and cultural spaces. Furthermore, it demonstrates how community leadership, articulated through solidarity and advocacy practices, can generate sustainable social and institutional impacts, offering significant contributions to public policy development, social practices, and academic studies on integration, superdiversity, and intercultural inclusion